Storia come campo e come dimensione del corpo: freccia e circolo, tradizione e innovazione in Maurice Merleau-Ponty - Iofrida, Manlio (Scenari, 2024)
Starting from some considerations about the present historical situation, characterized by the ecological crisis and the end of the globalization as it has been known in the last thirty years, an attempt is made to reintroduce the concept of history, against the idea of “the end of history” which had course since the Nineties. It is from this point of view that Merleau-Ponty’s theorization of history, especially in The Visible and the Invisible and in some courses of the College de France (Institution. Passivité, L’Origin of geometrie de Husserl), is reconsidered. A particular stress is given to the model of “circle-array”, which is present – even if not in these literal terms – in the philosopher’s theory of history and a parallel with the history’s models of Huizinga, Riegl and Kracauer is proposed, to clarify the concept of “simultaneity of times” and of “omnitemporality”, which are fundamental in Merleau-Ponty’s vision.